Nitrogen Disturbance Awakening the Intrinsic Activity of Nickel Phosphide for Boosted Hydrogen Evolution Reaction. Issue 16 (7th July 2022) - Yang, Caixia; Wang, Zhiqiang; Li, Zhendong; Pan, Yichen; Jiang, Linwei; Li, Caicai; Wang, Chao; Sun, Qingfeng
Abstract: Nickel phosphide (Ni2 P) has emerged as a promising candidate to substitute Pt‐based catalysts for hydrogen evolution reaction (HER) due to the hydrogenase‐like catalytic mechanism and concomitantly low cost. However, its catalytic activity is still not comparable to that of noble‐metal‐based catalysts, and innovative strategies are still urgently needed to further improve its performance. Herein, a self‐supported N‐doped Ni2 P on Ni foam (N−Ni2 P/NF) was rationally designed and fabricated through a facile NH4 H2 PO2 ‐assisted gas‐solid reaction process. As an HER catalyst in alkaline medium, the obtained N−Ni2 P/NF revealed excellent electrocatalytic performance with a distinctly low overpotential of 50 mV at 10 mA cm −2, a small Tafel slope of 45 mV dec −1, and long‐term stability for 25 h. In addition, the spectroscopic characterizations and density functional theory calculations confirmed that the incorporation of N regulated the original electronic structure of Ni2 P, enhanced its intrinsic catalytic property, optimized the Gibbs free energy of reaction intermediates, and ultimately promoted the HER process. This work provides an atomic‐level insight into the electronic structure modulation of metal phosphides and opens an avenue for developing advanced transition metal phosphides‐based catalysts. Abstract : Nitrogen doping : A novel and self‐supported nitrogen‐doped Ni2 P electrode (N−Ni2 P/Ni foam) is prepared through a one‐step NH4 H2 PO2 ‐assisted gas‐solid reaction process. Both experimental and theoretical studies prove that N doping regulates the electronic structure of pristine Ni2 P, resulting in optimized adsorption free energy of water and hydrogen and eventually accelerating the hydrogen evolution performance of Ni2 P.